2021
DOI: 10.1002/sia.6991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the molecular weight on the depth profiling of PMMA thin films using low‐energy Cs+ sputtering

Abstract: investigate the influence of the molecular weight of poly(methyl methacrylate) (PMMA) thin films coated on silicon wafer on the time-of-flight secondary ion mass spectrometry (ToF-SIMS) sputtering mechanisms and kinetics during depth profiling using low-energy monoatomic caesium ions. The sputtering yield volumes are determined as function of molecular weight, film thickness and beam energy. The results show that the sputtering yield volume decreases with increasing molecular weight M w down to a threshold val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In contrast, our results are obtained in the so-called static conditions (single impacts). In general, the values shown in Figure correspond to the results obtained with other type I and type II polymers bombarded with atomic projectiles in the kinetic energy range of interest. ,, …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, our results are obtained in the so-called static conditions (single impacts). In general, the values shown in Figure correspond to the results obtained with other type I and type II polymers bombarded with atomic projectiles in the kinetic energy range of interest. ,, …”
Section: Resultssupporting
confidence: 77%
“…In general, the values shown in Figure 3 correspond to the results obtained with other type I and type II polymers 20 bombarded with atomic projectiles in the kinetic energy range of interest. 23,57,58 The mass distributions of particles ejected from the investigated systems are shown in Figure 4. Since the emission efficiency does not depend on the overlayer thickness, and the ejection simulated by the Ar and Xe projectiles is similar, only the data for the He and Ar bombarded single-layer and fourlayer systems are shown.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, it has been reported that the surface roughness and sample temperature may influence sputtering phenomena. 19 , 20 We will investigate this topic in the future.…”
mentioning
confidence: 99%